Corporate Value Based on Corporate Social Responsibility and Good Corporate Governance - Komariatun Komariatun; Mutamimah Mutamimah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to analyze the role of GCG in moderating the influence of Economic CSR, Environmental CSR and Social CSR on Corporate Value. In this study use of purposive sampling method, using certain considerations relevant to the research objective. The number of samples obtained are 13 SOEs listed on Indonesia Stock Exchange in the 2017-2020. The data were analyzed using panel data regression with the Eviews program. The results of the study indicated that economic CSR has an effect on corporate value, however environmental CSR has no effect on corporate value and social CSR has a negative effect on corporate value. GCG can weakens the relationship between Economic CSR and corporate value and GCG does not moderate the relationship between Environmental CSR and corporate value, however GCG can strengthen the relationship between Social CSR and corporate value.